Contingencies in the effects of job-based pay dispersion on employee attitudes - Kepes, Sven; Jokela, Markus; Tenhiälä, Aino (John Wiley and Sons Inc, 2023)
When does pay dispersion elicit positive or negative employee attitudes? A review of the pay dispersion literature indicates a controversy around this vital question and suggests that numerous contingency factors moderate the effects of pay dispersion. In an empirical study of four Finnish companies consisting of 141 work units,we examine contingencies in attitudinal reactions to job-based pay dispersion among blue-collar workers. Based on archival pay data matched with employee survey responses (n = 536),we find that perceptions of pay basis legitimacy,task interdependence,and an individual's pay standing within the work unit explain the strength and direction of the relation between job-based pay dispersion and employee attitudes (i.e.,work engagement and organizational commitment). Our findings have implications for the design of pay systems and contribute to a better appreciation of the complexities underlying employee attitudinal responses to pay dispersion. © 2023 The Authors. Human Resource Management published by Wiley Periodicals LLC.
Keywords: article; blue collar worker; compensation; empiricism; employee; employee attitude; human; job analysis; major clinical study; perception; work engagement; Blue-collar jobs; Blue-collar workers; Compensation; Hierarchy; Job evaluation; Organizational commitment; Pay basis legitimacy; Pay dispersion; Pay structure; Status; Task interdependence; Work engagement; ODS 8 - Trabajo decente y crecimiento económico